# Give an equation for c not involving a.?

Combine c=4a-3 and 2b=3a-8

Relevance
• 1 month ago

c=4a-3--------(1)

2b=3a-8--------(2)

3(1)-4(2)

=>

3c-8b=-9+32

=>

3c=23+8b

=>

c=(23+8b)/3

• Philip
Lv 6
1 month ago

c=4a-3...(1), 2b=3a-8...(2).;

(2)---> a = (1/3)2(b+4) = (2/3)(b+4).;

Then (1)---> c = 4[(2/3)(b+4)] -3 = (8/3)b +(32/3) -(96/3) = (8/3)b -(64/3) = (8/3)(b-8);

ie., c = (8/3)(b-8).

• 1 month ago

An equation for c not involving a.

Combine c = 4a - 3 and 2b = 3a - 8

a = (c + 3)/4

• Ian H
Lv 7
1 month ago

12a = 3(c + 3) = 4(2b + 8)

3c = 8b + 23

• Jeremy
Lv 6
1 month ago

1)

c = 4a - 3 ===> c + 3 = 4a ===> a = (c + 3)/4.

2)

2b = 3a - 8 ===> 2b + 8 = 3a ===> a = (2b + 8)/3.

3)

If "a = (c + 3)/4" and "a = (2b + 8)/3", therefore:

(c + 3)/4 = (2b + 8)/3.

3 * (c + 3) = 4 * (2b + 8).

3 * c + 3 * 3 = 4 * 2b + 4 * 8.

3c + 9 = 8b + 32.

3c = 8b + 32 - 9.

3c = 8b + 23.

c = (8b + 23)/3 <=== ANSWER.

Or, alternatively: c = (8/3) * b + 23/3.

• 1 month ago

c = 4a - 3 and 2b = 3a - 8

The second equation can be re-arranged to make a the subject

so, 3a = 2b + 8

Hence, a = (2b + 8)/3

Putting this into the first equation for a gives:

c = 4(2b + 8)/3  - 3

or, c = 8b/3 + 32/3 - 9/3

so, c = 8b/3 + 23/3

Then, c = (8b + 23)/3....which gives c in terms of b

:)>

• 1 month ago

given c=4a-3, now 4a=3-c, => a=3-c/4  & similarly a=2b+8/3 , solve them

• 1 month ago

If you want to remove the "a", then solve one equation for "a" in terms of the other variable and substitute into the other equation.  This will give you a new equation with two unknowns, "b" and "c".  Then you can solve for c.

So we have:

c = 4a - 3 and 2b = 3a - 8

The first is already c in terms of a, so we want to leave that alone for now.  Solve the other one for a in terms of b:

2b = 3a - 8

2b + 8 = 3a

(2b + 8) / 3 = a

Now we can substitue that expression for "a" in the other equation:

c = 4a - 3

c = 4(2b + 8) / 3 - 3

Let's distribute the 4 and get a common denominator so we can simplify this:

c = (8b + 32) / 3 - 9 / 3

Now we can subtract the numerators:

c = (8b + 32 - 9) / 3

and simplify:

c = (8b + 23) / 3

or:

c = (8/3)b + 23/3

Either gives you c in terms of b.